Long term effects of exposure to automobile exhaust on the pulmonary function of female adults in Tokyo, Japan. Issue 4 (18th March 2004) - Sekine, K; Shima, M; Nitta, Y; Adachi, M
Abstract : Aims: To investigate the chronic effects of air pollution caused mainly by automobiles in healthy adult females. Methods: Respiratory symptoms were investigated in 5682 adult females who had lived in the Tokyo metropolitan area for three years or more in 1987; 733 of them were subjected to pulmonary function tests over eight years from 1987 to 1994. The subjects were divided into three groups by the level of air pollution they were exposed to during the study period. The concentrations of nitrogen dioxide and suspended particulate matter were the highest in group 1, and the lowest in group 3. Results: The prevalence rates of respiratory symptoms in group 1 were higher than those in groups 2 and 3, except for wheezing. Multiple logistic regression analysis showed significant differences in persistent phlegm and breathlessness. The subjects selected for the analysis of pulmonary function were 94, 210, and 102 females in groups 1, 2, and 3, respectively. The annual mean change of FEV1 in group 1 was the largest (−0.020 l/y), followed by that in group 2 (−0.015 l/y), and that in group 3 (−0.009 l/y). Testing for trends showed a significant larger decrease of FEV1 with the increase in the level of air pollution. Conclusions: The subjects living in areas with high levels of air pollution showed higher prevalence rates of respiratory symptoms and a larger decrease of FEV1 compared with those living in areas with low levels of air pollution. Since the traffic density is larger in areas with high air pollution, the differences among the groups may reflect the effect of air pollution attributable to particulate matter found in automobile exhaust.